Itch: an under‐recognized problem in psoriasis. (10th May 2019) - Elewski, B.; Alexis, A.F.; Lebwohl, M.; Stein Gold, L.; Pariser, D.; Del Rosso, J.; Yosipovitch, G.
Abstract: Psoriasis has historically been considered a nonpruritic dermatosis, in contrast with atopic dermatitis. Thus, itch has often been underappreciated and overlooked in psoriasis. However, increasing evidence over the past decade has shown that itch can be one of the most prevalent and burdensome symptoms associated with psoriasis, affecting almost every patient to some degree. Itch can involve the entire body, although it predominantly affects the legs, hands, back, body and especially the scalp. Uncontrolled itch can significantly impact all aspects of the well‐being and quality of life of the patient. While there has been some progress in trying to better understand the pathophysiology of itch in psoriasis, more research effort and interest are needed. This under‐recognition of itch in psoriasis is clearly reflected in the dearth of treatment options targeting itch despite significant advancement in treating the lesions themselves. Recently, however, clinical studies have begun to include itch as a study outcome. The resulting data have demonstrated concomitant antipruritic benefits and improved Psoriasis Area and Severity Index (PASI) scores with mainstay treatments for psoriasis, such as topical corticosteroids and vitamin D analogs, phototherapies, and various systemics and biologics. This article takes a closer look at this debilitating symptom, reviewing the available epidemiology data for psoriatic itch, presenting the current understanding of psoriatic itch pathophysiology and highlighting important clinical data for various treatment options for itch. Practical considerations for increasing the recognition of itch as well as improving its management in psoriasis are also provided.